Occupational morbidity in Russia: problems and solutions - Vadulina, N. V.; Gallyamov, M. A.; Devyatova, S. M. (Bezopasnostʹ tehnogennyh i prirodnyh sistem, 2020)
Introduction. The article presents the results of the analysis of the problems associated with occupational diseases in the country caused by adverse production factors. The facts of discrepancy between the official occupational diseases statistics and the assessment of the potentially possible number of them are established. The main reason for not registration of occupational diseases is the disinterest of the employer, employee and the commission, which conducts medical examinations, and also imperfection of legislative and standard base.Problem Statement. The purpose of this study is to develop measures to reduce the level of morbidity caused by professional activity.Theoretical Part. The problems associated with occupational diseases, factors that can and should solve the problem of ensuring the safety of production are considered, and measures are proposed to solve these problems.Conclusion. The importance of the official registration of occupational diseases, their investigation and prevention is shown. Ways to solve problems both at the state level and at the enterprise level are proposed. The probabilistic assessment of harmful production factors affecting the risk of occupational diseases are determined. Key dependencies in the formation of occupational diseases at each specific enterprise are identified and the improvement of the enterprise’s labor protection management system is proposed taking into account the risk of occupational diseases.